Near real-time analytics engine for vitals and environmental monitoring of first responders - José Pedro Dias de Almeida Machado (2020)
First Responders are on a daily basis exposed to extreme conditions not only because of their duties but also due to the type of environment in which they perform. If the exposure to these conditions is not monitored, it may cause several health problems in long and short-term. This exposure can be controlled through vitals and environmental sensors placed in these professionals. However, the collected data is not relevant if it is not analyzed and processed. This analysis has the most benefits the closer it is to the moment the data is collected, allowing a more informed decision making. The purpose of this thesis is to study and implement a service system in the cloud enabling near real-time processing of the data that was collected by the sensors. This system allows the dynamic change of the running data processing services through a web interface, which also allows changing the source of the data that is going to be processed, whether it is from services that are external to the system or that are read directly from files. For this purpose we need each service to be sufficiently isolated not to interfere with others, choosing to keep a service per container because it addresses the least expensive virtualization option. This solution allows each machine to have several services that share the same computational resources, as its allocation is abstracted by the chosen solution. This system allows not only the integration of processing methods that already exist but also presents enough modularity so that they can be developed and integrated new methods.